English Major Students’ Attitudes Towards The Use of Zoom Meeting for Online Learning in Learning English Speaking Skill - Nanda Amalia Putri; Maman Suryaman (Jurnal Ilmiah Profesi Pendidikan, 2022)
Many students may find it difficult to build good English speaking abilities due to the language’s complexity. The differences between English and the native tongue cause discomfort when speaking the new language in front of others. Therefore, Zoom Meeting application can be used by teachers to teach English, especially in teaching English speaking classroom. A case study research was conducted to explore English major students’ attitudes in using Zoom Meeting for online learning in learning English speaking skill. The data collection were collected by creating a questionnaire that consisted of 15 statements. The questionnaire was distributed via Google Form. The participants of this study were students of English Education Department from a state university in Karawang which is selected randomly about 9 students from second semester students. The result revealed that the use of Zoom Meeting applications make students understand some speaking class learning materials easily. However, in the other case, most of the them were bored with the implementation of online classes and lost of motivation to study during the COVID-19 pandemic. In conclusion, the majority of English major students’ had both positive and negative attitude toward the use of Zoom Meeting for online learning in teaching English speaking skills.